Parallel algorithms for solving linear systems with block-tridiagonal matrices on multi-core CPU with GPU - Akimova, Elena N.; Belousov, Dmitry V. (Journal of computational science, 2012)
► Block-tridiagonal linear systems in geoelectrics problems. ► Parallel algorithms for solving block-tridiagonal SLAE are proposed and implemented numerically on multi-core CPU with GPU. ► Investigation of efficiency and optimization of parallel algorithms are performed. For solving systems of linear algebraic equations with block-tridiagonal matrices arising in geoelectrics problems, the parallel matrix sweep algorithm, conjugate gradient method with preconditioner, and square root method are proposed and implemented numerically on multi-core CPU Intel with graphics processors NVIDIA. Investigation of efficiency and optimization of parallel algorithms for solving the problem with quasi-model data are performed.